EFFECTS OF FERMENTATION DURATION ON PHYSICOCHEMICAL AND ORGANOLEPTIC CHARACTERISTICS OF THREE AGARWOODS (Aquilaria) LEAVES TEA - Anisa Leksono; Erni Sofia Murtini (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2021)
Aquilaria is one of the plant genus-producing agarwood. Aquilaria leaves have pharmacological effects which the potential to be processed into black tea. The aim of this study is to determine the effect of fermentation duration on physicochemical and organoleptic characteristics of Aquilaria leaves tea. This study employed a Completely Randomized Design with two factors; the plant species (A. crassna, A. malaccensis, and A. subintegra) and fermentation duration (0 minutes, 70 minutes, and 90 minutes). Parameters analyzed including water content, total phenol, and antioxidant activity. Organoleptic tests were performed on the color, taste, and aroma of the brewed tea. The results summarized that A. subintegra had the highest total phenol and antioxidant activity, but the taste of the tea was not favored. A. crassna fermented 70 minutes and A. malaccensis fermented 0 minutes were the most preferred, but both have lower total phenol and antioxidant activity than A. subintegra.